Development of simplified inventory system with online synchronize capability - Choo, Wou Onn; Chua, Sook Ching; Chue, Wen Yeen; Lee, Lam Hong (2010)
This research describes the development of Simplified Inventory System (SIS), an online supported central monitoring system that provides integrated services to suppliers and customers in Electronic Commerce (EC). SIS system records order/transaction online and offline into a system which will be processed and subsequently updating the existing database with synchronization capability. Reports can be generated from the system to keep track of information in the database, thus provides the most updated information on the inventory that indicates the best possible action can be taken whenever system go offline.This research uses the system development methodology of ADDIE which consists of Analysis, Design, Development, Implementation and Evaluation.This methodology enables the SIS to be developed in a more simplified form to synchronize with existing online applications. A series of literature review is conducted to find out the problem statements and expectations from different parties to ensure the system fulfills the requirements of the suppliers and customers on producing a quality SIS system. With the advancement of current web-based technologies, SIS is to simplify the workload and more efficient in producing results compared to existing inventory systems.